2012
DOI: 10.4236/sm.2012.21002
|View full text |Cite
|
Sign up to set email alerts
|

Wives’ Work Hours and Marital Dissolution: Differential Effects across Marital Duration

Abstract: In this article, I ask: Does the effect of wives' work hours on marital dissolution change across marital duration? Using the first two waves of the National Survey of Families and Households (NSFH), I find only weak evidence that wives' work hours are associated with higher marital dissolution. The effect, however, is more positive and significant among long-term marriages. In addition, this study also tests whether couples' gender ideology and marital interaction explain this differential effect of wives' wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Therefore, one would expect that the more couples operate jointly in their leisure time, the lower their risk of union dissolution. Previous studies support this expectation (e.g., Booth et al 1984;Hill 1988;Gager and Sanchez 2003;Yucel 2012). Research is, however, sparse and has focused exclusively on marriage, thereby disregarding cohabiting couples.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, one would expect that the more couples operate jointly in their leisure time, the lower their risk of union dissolution. Previous studies support this expectation (e.g., Booth et al 1984;Hill 1988;Gager and Sanchez 2003;Yucel 2012). Research is, however, sparse and has focused exclusively on marriage, thereby disregarding cohabiting couples.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies analyzed data from earlier divorced respondents who reported lifestyles retrospectively (e.g., Poortman 2005), which suffers from problems of recall, or predicted proxies of divorce such as "discussing divorce" instead of its occurrence (e.g., Booth et al 1984). Studies that combined a prospective measure of lifestyles with the observed event of divorce often merely operationalized joint lifestyles as the amount of time spent together (Gager and Sanchez 2003;Presser 2000;Terling-Watt 2001;Yucel 2012). Such a measure not only provides little insight into the nature of this time, but is also obviously sensitive to the amount of leisure time in general (Kalmijn and Bernasco 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution of marital and cohabiting relationships can be explained by perceptions of work-life balance in a family household. Several correlational studies have noted that when work hours exceed the number of hours devoted to one's partner, it can escalate the conflict and lead to feelings of relational dissolution in marital and cohabiting relationships (Spitze & South, 1985;Voydanoff, 1998;Yucel, 2012). In particular, a longitudinal study has found that wives' excessive work hours positively correlate with marital dissolution.…”
Section: Work-life Balance and Relationship Dissolutionmentioning
confidence: 99%
“…In particular, a longitudinal study has found that wives' excessive work hours positively correlate with marital dissolution. However, this study has not controlled for any demographic variables, and examined only marital couples (Yucel, 2012). A lack of work-life balance highlights the inability to manage energy and time effectively, due to partners' work schedules in order to stabilize their long-term relationships (Tausig & Fenwick, 2001).…”
Section: Work-life Balance and Relationship Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation